Analisis Gender pada Manajemen Usaha Sektor Mikro (Studi Kasus Industri Pembuatan Gula Kelapa di Kabupaten Sleman) - Ninik Sri Rahayu (Jurnal Aplikasi Bisnis, 2017)
This study purposed to describe gender profile of the micro enterprise management from four aspects: productive activities, non productive activities, access and control, business effect and benefit. It also aimed to formulate strengthening strategy based on gender perspective. The research was performed in Sleman regency with 25 micro enterprises in brown sugar as research samples.Simple random sampling was chosen in the process of selecting lata and Harvard Analytical Framework was adopted to analysis it. The research discovered some findings. First, women have had dominant contribution in all activities, both in business management and in production process. Second, the profile of domestic activities such as cooking, shopping, maintaing household was majority organized by women. Third, women access and control over resources were higher than men. Fourth, the entire resoulrces and the production outcome were able to provide benefit for family members, particularly for women. Fifth, this industry was not only needed strengthening program in the term of technical assistance such as finance, marketing, and information but it also required spesific assistance programs to accomplish women gender practice.According to the research findings, it is essential to conduct training, directive counseling to socialize gender equality and equaly in micro industries. It is also vital to carry out women empowerment program to advance their productivity and welfare.